Repenser sociologiquement l’architecture à partir de ses médiations - Christophe Camus (Association Internationale des Sociologues de Langue Française, 2021)
This article is based on the career and research of a non-architect sociologist who teaches in architecture schools. It encourages us to rethink architecture from the point of view of communication situations or mediations that express, surround or accompany the practices of architects. Rather than approaching architectural activity by focusing on the concrete production of buildings or spaces, he focuses on the mediations that circulate from the agency to the public space, and that characterize this art of building. Questioning the sociologies of architecture in a media regime, the article invites us to switch from a sociology of the architect's profession that takes into account its communications, to a constructivist sociology of architecture.